Palliative approach in an oncology patient with oropharyngeal dysphagia: A case report - Ambiado-Lillo, Manuel Matías (Revista de Investigación en Logopedia, 2026)
Advanced cancer represents a highly complex clinical condition, frequently associated with progressive functional decline and impaired quality of life. Among its most relevant manifestations are swallowing disorders, which may be exacerbated as a consequence of contemporary oncological treatments, particularly immunotherapy. In this context, Triple M syndrome—characterized by the overlap of myocarditis, myositis, and myasthenia gravis induced by immune checkpoint inhibitors—constitutes a severe neuromuscular complication with direct impact on swallowing function. This article describes the speech-language pathology management of a clinical case involving a 67-year-old patient with advanced cancer and oropharyngeal dysphagia secondary to Triple M syndrome. The intervention was conducted within a palliative care framework, integrating compensatory strategies alongside rehabilitative-oriented orofacial myofunctional exercises, aligned with the patient’s goals and priorities. Systematic adherence to the therapeutic process resulted in a favorable evolution of swallowing performance, facilitating the transition from exclusive gastrostomy feeding to predominantly oral intake, with a positive impact on comfort and quality of life.